Traditional knowledge of medicinal mushrooms and lichens of Yuman peoples in Northern Mexico - Joshua Anthuan Bautista-González; Adriana Montoya; Robert Bye; Martín Esqueda; María de los Angeles Herrera-Campos (BMC, 2022)
Abstract Background Mushrooms and lichens are natural therapeutic resources whose millenary importance persists in indigenous and mestizo communities of Mexico. However, in this regard, in the northern part of the country there are few ethnobiological explorations. This study investigates the local knowledge of medicinal mushrooms and lichens used by Yuman peoples, whose native speakers are in imminent danger of extinction along with their biocultural heritage due to changes in their traditional primary activities and the usurpation of their ancestral lands. Methods Ethnographic techniques in the field and standard lichenological and mycological methods in the laboratory were used. Results Information was obtained on the medicinal use of 20 species, of which six are lichens of the genus Xanthoparmelia and 14 are non-lichenized fungi, mainly gasteroids. The latter are primarily used to treat skin lesions, while lichens are used in heart, urinary, and gastrointestinal diseases. The transmission of this local knowledge to future generations is discussed, as well as the intercultural cognitive convergence about the uses of medicinal mushrooms and lichens. Conclusions The Yuman peoples preserve knowledge, practices and beliefs around mushrooms and lichens. Although increasingly less used, they still form part of their culinary and traditional medicine; even some are also used as ludic and ornamental purposes, and as trail markers. Beyond the pragmatic importance of these organisms, traditional knowledge about them is an essential part of the cultural identity that the Yuman peoples strive to preserve.